The New Pope Episode 1-9 - Sorrentino, Paolo; Bigazzi, Luca; Law, Jude; Malkovich, John; Orlando, Silvio (Dazzler Media, 2020)
Pius XIII (Jude Law) is in a coma. After an unpredictable and mysterious time, the Secretary of State Voiello succeeds in the enterprise of having the charming, sophisticated and moderate English aristocrat Sir John Brannox (John Malkovich) placed on the papal throne with the name John Paul III. The new pope seems perfect, but he conceals secrets and a certain fragility. Quickly, he begins to realise that it will not be easy to replace the charismatic Pius XIII who, hanging between life and death, has become a Saint with thousands of faithful followers now idolizing him. Meanwhile, the Church is under attack from several scandals that risk irreversibly devastating the hierarchies of the Church, and the key principles of Christianity upon which they are based. As always, nothing is as it originally seems in the Vatican. Good and evil march arm in arm through this historic institution, right up until the final showdown ... [www.amazon.co.uk]
Keywords: Blu-Ray-Disc